Effect of cuff positioning on the accuracy of blood pressure measurement with automated electronic blood pressure monitors - Li, Ya (J Clin Hypertens (Greenwich), 2020)
It is recommended that the cuff should be wrapped around the upper arm with the midline of the bladder placed over the brachial artery during blood pressure (BP) measurement. However, in practice, the cuff of sphygmomanometers is often incorrectly placed. The authors aimed to assess the effect on the accuracy of BP measurement as to the placement of the cuff bladder by using oscillometric devices. Participants aged 18 years or older were enrolled. The center of the cuff bladder was placed directly over the brachial artery as the standard position (correct position), which was rotated by 90°medially (medial position), 90°laterally (lateral position), and rotated by 180°(contralateral position), respectively. The main outcomes were non‐invasive brachial BP in the four cuff positions, brachial artery pulse wave velocity, ankle‐brachial index, and invasive radial BP. Of 799 participants, 56.4% were men (60.37 ± 12.73 years), and of the 104 intensive care unit participants, 60.57% were men (57.78 ± 15.89 years). There were no significant differences in non‐invasive brachial BP among the four cuff positions (P > .1), and the mean BP differences between incorrect and standard cuff positions were within 1.0 mm Hg. BP of the incorrect positions was positively correlated with standard position (P < .001, r > .88) and showed good consistency. There was no effect on the accuracy of BP measurement as to the location of the midline of the cuff bladder by using oscillometric devices with a conventional cuff.